Analysis of VDC Performance and Its Interaction with Lean Construction in Peru - Romaní, Jordan (2025)
The present study aims to analyze the performance of Virtual Design and Construction (VDC) in construction projects in Peru, evaluating its interaction with Lean Construction. Through a systematic approach, it seeks to identify how these tools contribute to the success of projects, improving efficiency, collaboration and sustainability in the construction industry. The research uses a methodology based on data collection through surveys and review of case studies. This will allow obtaining a comprehensive view of the main challenges and benefits associated with the implementation of VDC and Lean Construction (LC) in the Peruvian context. It was identified that the benefits associated with the integration of VDC and LC are consistent with the existing literature, validating its ability to generate value, reduce waste and facilitate collaborative decision making. In addition, the role of Lean tools, such as the Last Planner System, in the consolidation of planning and control strategies was highlighted. This work contributes to reinforce the practical knowledge on the application of VDC in construction projects in Peru, providing professionals in the industry with insights into best practices, challenges, and strategies to optimize implementation.